2020
DOI: 10.1098/rsta.2020.0063
|View full text |Cite|
|
Sign up to set email alerts
|

Octane isomer dynamics in H-ZSM-5 as a function of Si/Al ratio: a quasi-elastic neutron scattering study

Abstract: Dynamical behaviour of n- octane and 2,5-dimethylhexane in H-ZSM-5 zeolite catalysts of differing Si/Al ratios (15 and 140) was probed using quasi-elastic neutron scattering, to understand molecular shape and Brønsted acid site density effects on the behaviour of common species in the fluid catalytic cracking (FCC) process, where H-ZSM-5 is an additive catalyst. Between 300 and 400 K, n -octane displayed uniaxial rotation around its long axis. However, the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The same simulations were ran at 653 K to match the temperature of the experiments carried out by Imbert and colleagues 33,33,34 . Furthermore, the third catalytic system -H-ZSM5 -was included, which was not measured experimentally due to the low probability of observing dynamics relating to catalysis over the instrumental timescale of OSIRIS, as observed with 2,5-dimethylhexane loaded into H-ZSM5 83 . H-ZSM5 has frequently been tested for its ability to convert biomass feedstocks 10,15,16,21,31 .…”
Section: Nanoscale Diffusivity At Catalytic Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same simulations were ran at 653 K to match the temperature of the experiments carried out by Imbert and colleagues 33,33,34 . Furthermore, the third catalytic system -H-ZSM5 -was included, which was not measured experimentally due to the low probability of observing dynamics relating to catalysis over the instrumental timescale of OSIRIS, as observed with 2,5-dimethylhexane loaded into H-ZSM5 83 . H-ZSM5 has frequently been tested for its ability to convert biomass feedstocks 10,15,16,21,31 .…”
Section: Nanoscale Diffusivity At Catalytic Temperaturesmentioning
confidence: 99%
“…33,34 Furthermore, a third catalytic system -H-ZSM5was Catalysis Science & Technology Paper included, which was not measured experimentally due to the low probability of observing dynamics relating to catalysis over the instrumental timescale of OSIRIS, as observed with 2,5-dimethylhexane loaded into H-ZSM5. 83 H-ZSM5 has frequently been tested for its ability to convert biomass feedstocks. 10,15,16,21,31 As with the other systems, the diffusion of 10% wt of p-and m-cresol throughout the zeolite framework was simulated over 5 ns, with the MSD plots for the simulations ran at 653 K shown in Fig.…”
Section: Nanoscale Diffusivitymentioning
confidence: 99%
“…Omojola et al [327] showed the importance of this factor while studying methanol and dimethyl ether in HZSM-5 zeolite. O'Malley et al also studied the rotational dynamics of octane and 2, 5-dimethylhexane in HZSM-5 as a function of its Si/Al ratio [328]. They showed that the rotational motions of both hydrocarbons were much more hindered when additional Brønsted sites (a lower Si/Al ratio) were present in the system, implying the importance of the composition of zeolite in the dynamic behavior of hydrocarbons in a zeolite.…”
Section: Possibilities and Future Challengesmentioning
confidence: 99%
“…More recently the quasielastic response to pressure of barocaloric materials was resolved [19]. QENS was also applied studying the diffusion of small molecules in framework materials for catalytic applications and attracted a growing user community [20,21]. Within softmatter and bioscience the relaxations and mobility of large molecules and the water environment were investigated [22][23][24].…”
Section: Introductionmentioning
confidence: 99%